Pengaruh Harga, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Kerupuk Cassava pada Umkm Bintang Anugrah Kota Mojokerto - Amelia Asma’ul Windasari; Nersiwad Nersiwad; Toto Heru Dwihandoko (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of price, product quality and brand image on purchasing decisions of cassava crackers at UMKM Bintang Anugrah, Mojokerto City. The type of research used is quantitative research, namely to test hypotheses and show the relationship between the variables analyzed. The data sources used in this study are primary and secondary data, in which the primary data is the result of an online questionnaire using a Likert scale, while the secondary data is obtained from analyzing books, information and sources that already exist and are related to research information. The population in this study were consumers who had bought Cassava Crackers at UMKM Bintang Anugrah. The sample in the study consisted of 85 respondents using the Hair at al formula with a sampling technique using a non-probability sampling technique with a purposive sampling method, namely a method where researchers select samples based on research knowledge about the sample to be selected. Processing of this research data includes validity test, reliability test, classic assumption test, multiple linear regression test, coefficient of determination test (R2), T and F test. The results of this study can be concluded that price has a significant and positive effect on purchasing decisions of (2.446 > 1.989), product quality has a significant and positive effect on purchasing decisions (3.020 > 1.989) and brand image has a significant and positive effect on purchasing decisions (4.223 > 1.989). And all independent variables have a significant and positive effect on purchasing decisions of (25.250 > 2.72).